Pertanggungjawaban Pidana Dalam Penyebaran Data Pribadi: Tinjauan Hukum Pidana Saat Ini - Padrisan Jamba; Irene Svinarky (LPPM Universitas Putera Batam, 2023)
In an increasingly digital era, the issue of theft and dissemination of personal data has become a profound global concern. This research focuses on criminal liability in the dissemination of personal data, with the aim of reviewing and analyzing the current criminal legal framework in addressing violations related to personal data. The research employs a normative juridical method, referencing various legislations, court decisions, and relevant legal literature. We also analyze recent changes and developments in criminal law concerning the dissemination of personal data. The results of this research depict the complexity of regulations related to handling cases of personal data dissemination. Factors such as the type of data involved, the intent of the perpetrator, and the impact on affected individuals are crucial considerations in determining the level of criminal liability. The research also discusses potential criminal sanctions that may be imposed on perpetrators of personal data breaches, including fines and imprisonment. Additionally, we identify challenges in enforcing laws related to personal data and provide insights into potential improvement efforts. This research provides valuable insights into how current criminal law addresses the issue of personal data dissemination and promotes better protection for individuals in an ever-evolving digital era.